STAR as a strategy of P5 / Astri Dwi Jayanti Suhandoko ... [et al.] - Suhandoko, Astri Dwi Jayanti; Islami, Anggun; Winahyu, Fitria Heri; Sulastri, Sulastri (Unit Penerbitan, Universiti Teknologi MARA, Perak, 2023)
The vision of Indonesian education is the realization of advanced humans who are sovereign, independent, and have noble character. One step to realizing this vision is implementing the Kurikulum Merdeka in 2021. One of the things that differentiates the Kurikulum Merdeka from the previous curriculum is the P5 program (Projek Penguatan Profil Pelajar Pancasila). P5 is character learning, which is separate from intracurricular education. As a new thing, there are still few references on implementing P5 in schools. Therefore, a simple strategy is needed so that P5 can be implemented more efficiently. Sekolah Penggerak, a pilot project in the Program Sekolah Pengerak (PSP), already consists of 3 batches, namely 1, 2, and 3. Among them are SDN Gebang Raya 2, Kota Tangerang implementing PSP Batch 1, SDN Buaran Mangga 2, and SDIT Al Istiqomah Kabupaten implementing PSP class 3. Implementation of P5 in SDN. Gebang Raya 2 Kota Tangerang took the topic "Stop Bullying Let's Caring" to reduce bullying behavior in schools. SDN. Buaran Mangga 2 Tangerang Regency took the topic " Vegetables are my Favorite food!" which aims to change the perception of elementary school children about vegetables being healthy food, and at SDIT Al-Istiqomah took the topic "Whoa! Recycling is Cool" which aims to equip students with skills processing waste and awareness of disposing of waste in its place. The three of Sekolah Penggerak use the STAR strategy to implement the P5 program. The STAR stages are the initial situation, challenges faced when carrying out the project, actions or activities carried out, and finally, the project results. The results of the P5 project implemented in the three schools showed the character of mutual cooperation and global diversity was realized in students as an embodiment of the identity of the Indonesian nation.